The phenyl vinyl ether–methanol complex: a model system for quantum chemistry benchmarking - Bernhard, Dominic; Dietrich, Fabian; Fatima, Mariyam; Pérez, Cristóbal; Gottschalk, Hannes C.; Wuttke, Axel; Mata, Ricardo A.; Suhm, Martin A.; Schnell, Melanie; Gerhards, Markus (Beilstein Journal of Organic Chemistry, 2018)
The structure of the isolated aggregate of phenyl vinyl ether and methanol is studied by combining a multi-spectroscopic approach and quantum-chemical calculations in order to investigate the delicate interplay of noncovalent interactions. The complementary results of vibrational and rotational spectroscopy applied in molecular beam experiments reveal the preference of a hydrogen bond of the methanol towards the ether oxygen (OH∙∙∙O) over the π-docking motifs via the phenyl and vinyl moieties, with an additional less populated OH∙∙∙P(phenyl)-bound isomer detected only by microwave spectroscopy. The correct prediction of the energetic order of the isomers using quantum-chemical calculations turns out to be challenging and succeeds with a sophisticated local coupled cluster method. The latter also yields a quantification as well as a visualization of London dispersion, which prove to be valuable tools for understanding the role of dispersion on the docking preferences. Beyond the structural analysis of the electronic ground state (S0), the electronically excited (S1) state is analyzed, in which a destabilization of the OH∙∙∙O structure compared to the S0 state is observed experimentally and theoretically.
Keywords: dispersion interactions; IR spectroscopy; quantum-chemical calculations; rotational spectroscopy; structure determination; weak hydrogen bonds